Pengaruh Pajak, Kepemilikan Asing, dan Ukuran Perusahaan Terhadap Transfer Pricing: Studi Kasus Pada Sektor Basic Materials dan Industrials yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021 - Widya Anggraini; Ratna Herawati; Dian Indriana Hapsari; Amalia Nur Chasanah (Universitas Veteran Bangun Nusantara, 2023)
The purpose of this study is to examine the effect of tax, foreign ownership and company size on transfer pricing. The data used in this study are secondary data and quantitative research methods. This study uses the observation method for the company`s financial reports and annual reports. This research focuses on basic materials and industrials sector companies listed on the IDX in 2017-2021. The sampling method used purposive sampling. This study uses SPSS 25 to analysis 175 observational data. Data analyzed using descriptive statistics, model feasibility test, classic assumption test, logistic regression analysis, and hypothesis testing. Research has shown that taxes have no influence on transfer pricing, foreign ownership and company size affect transfer pricing.